The Impact of Social Class Solidification on the Educational Opportunities of the Next Generation in the Philippines and the Barriers to Social Mobility in Primary Education - Marisol C. Muñoz-Carrasco (Research and Advances in Education, 2024)
This paper explores the impact of social class solidification on the educational opportunities of the next generation in the Philippines, focusing specifically on primary education and the barriers to social mobility faced by children from low-income families. Despite recent economic growth, the Philippines remains deeply stratified, with income inequality and social class divisions reinforcing each other. This entrenched disparity limits access to quality education for disadvantaged students, exacerbating the cycle of poverty. Key barriers include economic constraints, underfunded public schools, language mismatches, and limited access to early childhood education, all of which contribute to lower academic achievement and higher dropout rates among poor students. The long-term effects of these barriers perpetuate inequality, hinder the development of a skilled workforce, and contribute to social instability. The paper argues that systemic reforms, such as increased investment in public education, targeted support for disadvantaged students, language and curriculum reforms, and expanded access to early childhood education, are critical to breaking this cycle. By addressing these barriers, the Philippines can create a more equitable education system that enables upward social mobility and promotes long-term social and economic stability.